Structural degradation mechanisms and modulation technologies of layered oxide cathodes for sodium‐ion batteries. Issue 1 (14th July 2022) - Song, Tianyi; Wang, Chenchen; Lee, Chun‐Sing
Abstract: Renewable energies, such as solar and wind, have been explored and widely applied for alleviating problems associated with the depletion of fossil fuel resources and environmental pollution. The intermittent and fluctuating features of these renewable energies require development of efficient energy storage and conversion systems. Sodium‐ion batteries (SIBs) are considered one of the most promising candidates for large‐scale energy storage due to the low cost and earth abundance of sodium resources. A major challenge for the practical application of SIBs is the development of appropriate cathodes with high energy densities and cycling stabilities. Layered oxide cathodes have received significant attention because of their relatively simple synthetic routes and high capacities stemming from their layered structures. However, they often suffer from moisture sensitivity and structural degradation upon repeated Na + insertion/extraction, leading to severe performance fading. This review summarizes and discusses the degradation mechanisms of these layered oxide cathodes and modulation strategies for addressing the stability issues. Understanding the mechanisms behind structural instability would provide better insight for improving SIBs' cathode materials, which has critical implications for the designs and applications of SIBs as renewable energy systems. Abstract : In this review, the main degradation mechanisms of layered oxide materials are analyzed, including Na + /vacancy ordering, irreversible phase transitions, and transition‐metal ion migration/dissolution. Relative modulation strategies are also summarized, providing an in‐depth understanding of the relationship between material structures and electrochemical performances to help design suitable cathode materials for sodium‐ion batteries.